Development and validation of the Adolescent Family Functioning Scale in Malaysia - Chin, Wen Cong (2023)
Family functioning is a culturally sensitive construct that has been related to various adolescent psychological outcomes (e.g., depression, life satisfaction, and emotional well-being). To better understand family functioning in Malaysian adolescents, a reliable and valid measurement of family functioning is needed. Therefore, the present research aims to develop and validate an indigenous instrument, the Adolescent Family Functioning Scale (AFFS), to measure Malaysian adolescents’ perceptions of family functioning. An exploratory sequential mixed method was adopted to collect the data in three studies (i.e., Study 1: item development, Study 2: scale development, and Study 3: scale validation). Study 1 explored Malaysian adolescents’ perceptions of family functioning through in-depth semi-structured interviews (N = 13). The thematic analysis revealed five dimensions of adolescent family functioning: (1) family culture, (2) family cohesiveness, (3) family relationship, (4) family affection, and (5) family pride. Based on the dimensions, an item pool consisting of 107 items was generated. To establish the content validity, a panel of five experts rated the essentiality of each item in reflecting adolescents’ family functioning, resulting in a 50-item preliminary version of the AFFS. In Study 2 (N = 733), exploratory factor analysis revealed three factors: Family Relationship, Family Cohesiveness, and Family Pride. Each factor’s top five items with the highest factor loadings were selected, resulting in a three-factor 15-item AFFS. Study 3 (N = 400) then examined and compared the hypothesized three-factor model, one-factor model, and three-factor second-order model through confirmatory factor analysis on the selected 15 items. Among these models, the three-factor model demonstrated the best fit to the data and hence it is preferred. Besides showing satisfactory internal consistency, different types of validity of the scale have also been established. In terms of construct validity, both convergent and discriminant validity of the AFFS has been established using the Fornell-Larcker criterion (Fornell & Larcker, 1981). For convergent validity, all subscales either had an Average Variance Extracted (AVE) value greater than .50 or a composite reliability coefficient greater than .70. For discriminant validity, all subscales had AVE’s square roots greater than their correlation pairs. Moreover, all subscales were negatively associated with the Depression subscale of the Depression, Anxiety, and Stress Scales 21 Items (Lovibond & Lovibond 1995) and positively associated with the Satisfaction With Life Scale (Diener et al., 1985), thus supporting the concurrent validity. Taken together, the 15-item AFFS appears to be an appropriate and useful family functioning instrument for adolescents in the context of Malaysia. Local mental health professionals and researchers are recommended to utilize the AFFS as a tool to assess the adolescent’s family functioning.